Isolation, Culture and Differentiation of Primary Acinar Epithelial Explants from Adult Murine Pancreas - Clara Lubeseder-Martellato (Bio-Protocol, 2013)
The adult pancreas possesses an intrinsic developmental plasticity whereby acinar cells can convert into ductal structures under some pathological conditions. Acinar tissue can be isolated from murine pancreas and kept in three-dimensional collagen culture. Acinar to ductal metaplasia can be induced in primary acinar epithelial explants by treatment with growth factors. This method can be utilized in ex vivo studies involving pancreatic epithelial differentiation.